Pemberian Hak Pengelolaan Kepada Desa Adat Dalam PP 18 Tahun 2021: Telaah Terhadap Teori Kemanfaatan Hukum - Mahulette, Abraham Julius Albert; Laturette, Adonia Ivone; Pietersz, Jemmy Jefry (Jurnal Saniri, 2025)
A land title certificate is proof of legal control and/or ownership of a plot of land. Through land registration, it will provide certainty about who holds the rights to the land. The subjects of land rights are individuals and legal entities, including customary law community units (customary villages). Through PP 18 of 2021, management rights are defined as a type of right that can be attached to land within the control area of a traditional village (ulayat land) with the traditional village as the subject of the right. The issuance of management rights certificates in the name of traditional villages is expected to provide significant benefits in improving the welfare of traditional communities.The aim of this research is to examine and analyze the theory of legal benefit in the implementation of the granting of management rights to traditional villages in PP 18 of 2021. The research method used in this research is normative juridical or library legal research methods.The implementation provisions for granting management rights to traditional villages in PP 18 of 2021 based on the theory of legal benefit are only provisions on paper which have been successfully promulgated but cannot be implemented and do not bring benefits to traditional villages so the government must immediately review these arrangements.